2020
DOI: 10.3390/cells9112419
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Tissue-Derived Stromal Cells Suppress Human, but Not Murine Lymphocyte Proliferation, via Indoleamine 2,3-Dioxygenase Activity

Abstract: Over recent years, mesenchymal stromal cells (MSC) have gained immense attraction in immunotherapy, regenerative medicine and tissue engineering. MSC microenvironment modulation occurs through synergy of direct cell–cell contact, and secreted soluble factors and extracellular vesicles (EV). MSC-derived EV have been suggested as cell-free immunomodulatory alternative to MSC; however, previous findings have challenged this. Furthermore, recent data suggest that evaluating the mechanism of action of human MSC (hM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 64 publications
8
52
0
Order By: Relevance
“…The main mechanism involved in human ASC-mediated inhibition of T cell proliferation is the induction of IDO expression, which enzymatically degrades tryptophan, required for T cell proliferation, to kynurenine, a direct inhibitor of T cell proliferation [ 31 ]. To confirm this, IDO was measured in cocultured ASC and kynurenine concentrations in coculture CM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main mechanism involved in human ASC-mediated inhibition of T cell proliferation is the induction of IDO expression, which enzymatically degrades tryptophan, required for T cell proliferation, to kynurenine, a direct inhibitor of T cell proliferation [ 31 ]. To confirm this, IDO was measured in cocultured ASC and kynurenine concentrations in coculture CM.…”
Section: Resultsmentioning
confidence: 99%
“…IDO is a catabolic enzyme which converts tryptophan to kynurenine [ 40 ]. In a previous study, we showed that increased IDO activity in ASC with subsequent tryptophan reduction and increasing kynurenine levels in their conditioned media was related to suppression of T cell proliferation in vitro [ 31 ]. In line with that, our data show that ASC from stimulated cocultures express higher levels of IDO than the ones from not stimulated cocultures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, using IL-17, MSCs increase the production of IL-6, which suppress T cell proliferation and inhibits Th1 cytokines production [ 119 ]. Instead, when primed with interferon gamma (IFN-γ), MSCs mainly produce indoleamide 2,3-dioxygenase (IDO) (a crucial factor able to suppress lymphocytes proliferation) [ 120 ], and also secrete key regulators of immunomodulation, such as prostaglandin E2 (PGE2), HGF, TGF-β and MCP-1. Furthermore, an increase of MHC I and II expression and of co-stimulatory molecules was also showed [ 121 ].…”
Section: Main Msc Priming Strategies To Enhance the Production Ofmentioning
confidence: 99%
“…The inhibition of the proliferation of T and B cells and the maturation of monocytes promotes the production of Tregs and M2 macrophages. Studies have shown that when the paracrine mechanism of MSCs is activated, they can directly secrete anti-inflammatory cytokines, such as indolamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), nitric oxide (NO), HLA-G, transforming growth factor-β (TGF-β), and vascular endothelial growth factor (VEGF) ( 19 , 20 ). These cytokines affect the number of immune cells and achieve the effect of suppressing the immune response.…”
Section: The Immunosuppressive Effect Of Mscs and Its Mechanismmentioning
confidence: 99%